A Narrative Inquiry of an Indonesian Prospective Teacher’s Teaching Experiences: Probing Language Teaching Awareness - Zehan Agustia Ainussamsi; Arini Nurul Hidayati; Dede Pertamana; Fuad Abdullah (STAI Hubbulwathan Duri, 2021)
This narrative inquiry aims at exploring the development of language teaching awareness experienced by a prospective teacher during teaching practicum. In this respect, the study provided insight for student-teachers to have a better understanding of their language teaching practice under certain kinds of circumstances. The participant of this study was a student-teacher majoring in English Education Department at Siliwangi University, Indonesia. She had already conducted a teaching practice in one junior high school in Tasikmalaya, West Java, within 2 months of teaching. The collected data from personal diaries written during the period of teaching, semi-structured interviews, and open-ended questionnaires were being processed qualitatively. The findings reported four primary themes emerging throughout the scrutiny of the development in language teaching awareness, namely (1) the dynamic feeling towards the language teaching practice, (2) the adaptability towards the language teaching activities in certain kinds of circumstance, (3) the ability to adjust with diverse teaching circumstances, (4) realization of the pedagogical implication of teaching beliefs and practices. Briefly stated, language teaching awareness explored through self-awareness can promote self-reflection, self-regulation, and self-evaluation.